2017
DOI: 10.5785/33-2-740
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the best: reading literacy development practices at a high-performing primary school

Abstract: While it is of utmost importance to scrutinise reading literacy development practices at South

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Reading comprehension is essential for reading because readers must have the ability to understand reading material that already read before 11 . Comprehension is fundamentally the goal of both reading and listening 12,13 .…”
Section: Reading Comprehensionmentioning
confidence: 99%
“…Reading comprehension is essential for reading because readers must have the ability to understand reading material that already read before 11 . Comprehension is fundamentally the goal of both reading and listening 12,13 .…”
Section: Reading Comprehensionmentioning
confidence: 99%
“…Without strong reading literacy development, learners have to battle to be successful in their educational progression throughout schooling which has dire consequences for their future prospects. Therefore, reading literacy needs to be a central school activity (Zimmerman, 2018). This study investigated factors affecting reading literacy looking at the relationship between instructional materials and pupils' English reading literacy.…”
Section: Introductionmentioning
confidence: 99%
“…In African countries reports reveal that reading literacy is a still a big challenge. For instance, it has been reported that in South Africa learners have reading problems, regardless of which language they read in (Zimmerman, 2018). In Ethiopia, an early grade reading assessment carried out in May and June 2010 by the Ministry of Education (MOE), RTI International, members of the Education and Training Quality Assurance Agency (ETQAA), and the Improving Quality in Primary Education Program (IQPEP) in a collaboration revealed that pupils reading capacity was below the expected level (Teshome, 2014).…”
Section: Introductionmentioning
confidence: 99%